2007
DOI: 10.1002/lsm.20573
|View full text |Cite
|
Sign up to set email alerts
|

Using optical coherence tomography to evaluate skin sun damage and precancer

Abstract: Background and Objectives-Optical coherence tomography (OCT) is a depth resolved imaging modality that may aid in identifying sun damaged skin and the precancerous condition actinic keratosis (AK).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 15 publications
4
99
1
2
Order By: Relevance
“…[9][10][11][12][13][14] A number of clinical studies have suggested that OCT might be useful for noninvasive diagnosis of skin disorders such as inflammatory and bullous skin diseases and to assess wound healing. 15,16 Several reports to date have examined the use of OCT imaging of NMSC. Previous studies demonstrate OCT images of BCC, SCC, and actinic keratoses (AK) and have correlated these findings with standard histology.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] A number of clinical studies have suggested that OCT might be useful for noninvasive diagnosis of skin disorders such as inflammatory and bullous skin diseases and to assess wound healing. 15,16 Several reports to date have examined the use of OCT imaging of NMSC. Previous studies demonstrate OCT images of BCC, SCC, and actinic keratoses (AK) and have correlated these findings with standard histology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the feasibility of machine learning tools was investigated in several studies [215,216]. Higher diagnostic accuracy compared to human observers could be achieved in some cases, demonstrating the potential as well as the need for improvement of these methods.…”
Section: Dermatologymentioning
confidence: 99%
“…Because the scattering properties do not change significantly for different wavelengths, this information could still be very interesting for obtaining information as correct as possible regarding the skin optical properties. OCT and confocal laser scanning microscopy have, for instance, been used to measure the thickness of stratum corneum and epidermis [136] as well as photodamage caused by Sun exposure [137]. Although OCT usually uses near infrared radiation in order to get depth sensitivity, it should be able to assess the relative strength of scattering in different skin layers.…”
Section: Instrumentations and Techniques To Measure Light Transmissiomentioning
confidence: 99%